2016
DOI: 10.1186/s12889-016-3073-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with anemia in school children from Maceió, northeastern Brazil

Abstract: BackgroundAnemia is a major public health problem in preschool children in Alagoas, Brazil, especially in the younger population, because of a positive correlation between hemoglobin level and age. However, due to the lack of studies, it is not known how widespread this condition is among older children or how it is associated with socioeconomic status. The aim of this study was to investigate the prevalence of and factors associated with anemia in school children from the city of Maceió, Alagoas state, Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
6
6
3
1
Order By: Relevance
“…Consequently, there is a mild public health problem in the study area that should be addressed using appropriate preventive methods as anemia leads to child morbidity and mortality [ 39 ]. This finding is comparatively close to other local studies carried out at Mekelle (11%) [ 30 , 41 ], but higher than the study done at Addis Ababa (5.83%) [ 42 ]. Also this study was comparatively close to other local studies carried out in Lithuania (10.1%) [ 43 ], Serbia (10.8%) [ 44 ], Mexico (12%) [ 45 ], and Brazil (9.3%) [ 41 ].…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, there is a mild public health problem in the study area that should be addressed using appropriate preventive methods as anemia leads to child morbidity and mortality [ 39 ]. This finding is comparatively close to other local studies carried out at Mekelle (11%) [ 30 , 41 ], but higher than the study done at Addis Ababa (5.83%) [ 42 ]. Also this study was comparatively close to other local studies carried out in Lithuania (10.1%) [ 43 ], Serbia (10.8%) [ 44 ], Mexico (12%) [ 45 ], and Brazil (9.3%) [ 41 ].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the prevalence seen in this study was higher than those of studies conducted in countries, such as the Siauliai region of Lithuania (10.1%) [ 27 ], Serbia (10.8%) [ 34 ], Mexico (12%) [ 35 ], and Brazil (9.3%) [ 36 ]. This discrepancy might be due to the variability of risk factors across different geographic regions, plus lower socioeconomic and nutritional status of SC in this study area than in the other settings.…”
Section: Discussioncontrasting
confidence: 67%
“…In the present study, we found that girls and rural children had lower hemoglobin concentration and a higher prevalence of anemia, which was consistent with a study conducted in India [24]. One possible reason may be due to the difference in pubertal development between boys and girls, as girls lose blood during menstruation and thus have a higher requirement for hemoglobin and iron [20,25].…”
Section: Discussionsupporting
confidence: 91%